Selected aspects of the economics surrounding equine disease - Kibler, Michelle L., author; Thilmany, Dawn, advisor; Pendell, Dustin, committee member; Costanigro, Marco, committee member; Traub-Dargatz, Josie, committee member (Colorado State University. Libraries, 2016)
The equine industry, from an economic perspective, is largely understudied with much of the existing research conducted on economic contribution studies (College of Agriculture, Food and Environment, University of Kentucky, 2013; Rephann, 2011; Conners et al., 2011; Deloitte Consulting LLP, 2005; Swinker et al., 2003) and the Thoroughbred sector of the industry (Maynard and Stoeppel, 2007; Poerwanto and Stowe, 2010; Plant and Stowe, 2013). Few studies have investigated the economic impacts of equine disease and/or equine disease outbreaks to individuals, regions, or states (USDA-APHIS-VS, 2003; Conners et al., 2011). This collection of studies aims to contribute to existing equine economic research by investigating the impacts of equine disease outbreaks in a variety of ways that complement and reinforce each component part’s findings. Equine owner’s experience two major types of costs when their horse has an infectious disease: direct costs of treating the horse for the disease (e.g., veterinarian expenses) and indirect costs (e.g., lost daily use of the horse). Utilizing survey data collected nationwide, estimates of daily horse use value (DHUV), as well as, respondent preferences regarding disease treatment options was obtained. Results suggest that the average horse owner is willing to pay between $11.99 and $17.84 to reduce the number of non-use (rest) days required. Respondents showed preferences for administration of oral medications over intramuscular injection medications, all else equal, and a preference for treatments requiring fewer number of doses per day. To expand upon the estimated DHUV, a survey of equine owners/riders/trainers, etc. provides data to estimate the lost DHUV experienced by respondents when their horse develops a disease as it relates to equine events. Results suggest DHUV, of those surveyed, to be impacted by income level, the frequency of equine events attended by distance and whether a planned equine event is upcoming or not. An important contribution to the previous study estimating daily use values of equids is the incorporation of a timing aspect related to equine events (i.e., length of time until a planned equine event). This generated the expected results and informed the conclusion that DHUV does vary as days until the next event decreases. As anticipated, equine owners assigned a higher daily value the use of their horse when an event was three weeks away compared to when there was no immediate event, and more specifically, the daily value increased by a difference of $4.14. In addition to effects on the equine owners, there are economy-wide implications from equine disease outbreaks as well. As one example, equine events drive tourism for the local economies for locations where th+H4ey are held, by generating revenue to multiple local industries. The economic impact from tourism activities surrounding equine events includes monies spent by event spectators, exhibitors and volunteers who reside outside the region and the “inflow of non-resident monies” used to purchase food/drink, lodging, fuel and gifts/souvenirs within the area of the event. Recent disease outbreaks in Colorado and other locations in the United States have caused equine travel restrictions, quarantines and the cancellation of equine events. Using survey data collected at a nationally attended equine event along with existing estimates of event attendee expenditures, the economic losses associated with canceled or reduced attendance at equine events are estimated. Loss estimates for the total effect from canceled or compromised attendance for this one national event range between $500,000 and $107 million depending on assumptions of the nature and severity of the outbreak.
Keywords: equine economics; equine disease; willingness-to-pay